2015
DOI: 10.4103/1596-3519.149897
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of young adults with stroke in Ilorin Nigeria

Abstract: The incidence of hemorrhagic CVA (ICH and SAH combined) was slightly higher than ischemic CVA in this study. Lacunar infarcts in the basal ganglia and also ICH in the basal ganglia were the most common patterns, both are strongly linked to hypertension. A diagnostic protocol of stroke in young adults, to include neuroimaging and other ancillary investigations is advocated for stroke in young adults as some of the etiologies are treatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…The age distribution revealed an increase in stroke prevalence with increase in age as 68% of the patients were between age range of 41 -50 years. This is similar to other hospital based studies in Nigeria [5] [15]. This is not surprising as increasing age is an established risk factor for stroke.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The age distribution revealed an increase in stroke prevalence with increase in age as 68% of the patients were between age range of 41 -50 years. This is similar to other hospital based studies in Nigeria [5] [15]. This is not surprising as increasing age is an established risk factor for stroke.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to the 59% for cerebral infarct and 41% for hemorrhagic stroke reported by Owolabi et al [5] but in variance with Oyinloye et al [15] who reported 48.3% for cerebral infarct and 51.7% for hemorrhagic stroke and Sarfo et al [11] who reported 47.5% and 52.5% for ischemic and Hemorrhagic strokes respectively. The variance could stern from the fact that Oyinloye et al [15] reported neuroimaging results at a neuroimaging centre which could be biased as hemorrhagic strokes, which is usually more severe are more likely to do neuroimaging than the ischemic counterpart. Sarfo et al [11] did a multicentre study in Ghana and Nigeria with larger sample size which excluded southeastern Nigeria where this study was carried out.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Few stroke persons were opportune to have a CT scan viz: 5.83% 24, 11.11% [62] in Nigeria, 10% from Madagascar [63] and even 0% from Gambia [64]. More recently, the percentages are increasing gradually as one Nigerian study showed that 40.8% patients had CT brain, while 5.6% had magnetic resonance imaging (MRI) [65] and 34.9% in Zimbabwe [60]. Yet another Nigerian study on stroke in the young, all the 69 (100%) patients had a brain CT scan [66].…”
Section: Action Taken In the Care Of Stroke In Sub Saharan Africamentioning
confidence: 99%
“…Neuroimaging is the technique used in the diagnosis and management of the AIS. It plays a major role, as it helps in the differentiation of the hemorrhagic and ischemic stroke where it is important in further management ( 3 ). Despite the therapeutic advances in recurrent ischemic stroke management, it affects the quality of life in most people.…”
Section: Introductionmentioning
confidence: 99%